(untitled) (Research, Society and Development, 2022)
Objective: To identify scientific evidence published from 2020 to December 2021 on the management of breastfeeding and skin-to-skin contact in women with COVID-19 in the immediate puerperium. Methods: This was an integrative literature review of the electronic databases: The US National Library of Medicine, The Cumulative Index to Nursing and Allied Health Literature and Web of Science. The search was carried out on January 1, 2022. Results: 117 articles were found, 18 of which were selected for analysis. The studies evaluated revealed differences in the health team’s conducts that varied between the practices recommended by the World Health Organization for maintaining breastfeeding and skin-to-skin contact, separation of the mother-child dyad, discouragement of breastfeeding, and mixed or artificial breastfeeding. In the research findings that showed the adoption of breastfeeding and skin-to-skin contact, there were no intercurrences and/or neonatal complications, which reinforces the safety of the practices. Conclusion: It was evidenced that the maintenance of exclusive breastfeeding and skin-to-skin contact receded during the pandemic by COVID-19. This study reiterates that breastfeeding and skin-to-skin contact are safe practices and there are more benefits and advantages of encouraging them than the expected harms of prohibitive conduct.